SPi-Bot : A Gesture Controlled Virtual Telepresence Robot - Swasthik M., C. T. Pawan, Hithaishree Shankar, Harshitha V., Vinay N. A. (International Journal of Modern Agriculture, 2021)
In today’s world, telepresence technology is thriving andwe can see its applications in a wide range. The meaning of â€œVIRTUALâ€ is being in effect though actually not. With the advent of telepresence mankind has stepped into a new era of technology. Telepresencecan be defined as a group of technologies thatenables a person to feel his environment via tele robotics even though that person is not physically present. This paperis a detailed report of agesture-controlled spider robot incorporated with telepresence which when interfaced with a handheld device provides a view of the environment, thus giving a feeling of being actually present even though not. The primary goal is to allow the user to have a near world experience even if he is not physically present.